EULAR points to consider for the use of imaging to guide interventional procedures in patients with rheumatic and musculoskeletal diseases (RMDs). Issue 6 (10th December 2021) - Dejaco, Christian; Machado, Pedro M; Carubbi, Francesco; Bosch, Philipp; Terslev, Lene; Tamborrini, Giorgio; Sconfienza, Luca Maria; Scirè, Carlo Alberto; Ruetten, Sebastian; van Rompay, Jef; Proft, Fabian; Pitzalis, Costantino; et al.
Abstract : Objectives: To develop evidence-based Points to Consider (PtC) for the use of imaging modalities to guide interventional procedures in patients with rheumatic and musculoskeletal diseases (RMDs). Methods: European Alliance of Associations for Rheumatology (EULAR) standardised operating procedures were followed. A systematic literature review was conducted to retrieve data on the role of imaging modalities including ultrasound (US), fluoroscopy, MRI, CT and fusion imaging to guide interventional procedures. Based on evidence and expert opinion, the task force (25 participants consisting of physicians, healthcare professionals and patients from 11 countries) developed PtC, with consensus obtained through voting. The final level of agreement was provided anonymously. Results: A total of three overarching principles and six specific PtC were formulated. The task force recommends preference of imaging over palpation to guide targeted interventional procedures at peripheral joints, periarticular musculoskeletal structures, nerves and the spine. While US is the favoured imaging technique for peripheral joints and nerves, the choice of the imaging method for the spine and sacroiliac joints has to be individualised according to the target, procedure, expertise, availability and radiation exposure. All imaging guided interventions should be performed by a trained specialist using appropriate operational procedures, settings and assistance by technical personnel. Conclusion: These are the first EULAR PtC to provide guidance on the role of imaging to guide interventional procedures in patients with RMDs.